Pneumothorax Treatment in Low-Resource Hospitals: Intercostal Drainage Remains the Primary Approach - Dr. Shagun; Dr. Sunil Sharma; Dr. Malay Sarkar; Dr. RS Negi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Ambulatory needle aspiration and outpatient one-way valves are increasingly recommended for uncomplicated pneumothorax, but the feasibility and effectiveness of such pathways in resource-constrained hospitals are uncertain. Objectives: To describe first-line treatment patterns, early radiographic success and procedure-related complications for all pneumothorax episodes presenting to an Indian district-level teaching hospital over 12 months. Methods: Prospective audit of 111 consecutive pneumothorax episodes (November 2020–October 2021). Interventions were categorised as (i) observation, (ii) oxygen, (iii) needle aspiration + oxygen, or (iv) intercostal drainage (ICD; 14 F pigtail). Primary outcome was full lung re-expansion on erect chest radiograph two hours after initial management. Secondary outcomes included early complications and hospital length of stay. Categorical variables were compared with χ²/Fisher’s exact test; p < 0.05 was significant. Results: ICD was performed in 98/111 episodes (88.3 %) independent of pneumothorax size. Two-hour full re-expansion occurred in 70/98 ICD (71.4 %) versus 5/13 non-ICD (38.5 %) (p = 0.02). Sub-cutaneous emphysema developed in 63/111 (56.8 %)—clinically minor in all; traumatic ICD insertion in 9/98 (9.2 %). No re-expansion pulmonary oedema or deaths occurred. Median hospital stay was five days (IQR 3–7), accounting for 680 inpatient bed-days annually. Conclusions: Despite guideline preference for ambulatory care, small-bore ICD remains the pragmatic and effective first-line therapy in low-resource hospitals, achieving rapid lung re-expansion with acceptable morbidity. Adapted outpatient aspiration protocols—requiring minimal equipment and tailored to tuberculosis-COPD overlap—deserve formal evaluation to ease bed pressures.